Adoption of Knowledge Management System: A Study on How IGracias Should be Adopted for Telkom Campus - Dewi Rahmawati; Noerma Pudji Istyanto; Muhammad Nasrullah (Jurnal KomtekInfo, 2020)
IGraciass is an integrated academic and non-academic management information system from the Telkom Education Foundation (YPT). Based on the vision and mission, the strategy and tagline of the Telkom Education Foundation is "The Leader of ICT Education Provider" and the spirit of digital transformation for Indonesia, I-Graciass must be adopted and implemented in all higher education institutions (lemdikti) under the auspices. The YPT. However, the facts on the ground the adoption and implementation process of I[1]Graciass in each of these higher education institutions are not easy matters. Many features, ease of use of technology and the system interface needed to access the system are important factors in the success of the system. For this reason, this research was conducted with the aim of facilitating the adoption process of IGraciass in all higher education institutions of the Telkom Education Foundation (YPT) according to the respective needs of the educational institutions under the auspices of YPT. This research was carried out using the mixing method both qualitatively and quantitatively, then the researcher also developed a qualitative research instrument to conduct a survey of the users to determine which channels were effective in the process of transferring knowledge. The results show that to minimize the risk of failure in adopting a knowledge management system, companies need to select a system based on the functional, non-functional and transition requirements for the system, as well as the strength and capacity of the organization.